2011
DOI: 10.2466/01.28.pr0.108.3.717-736
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Satisfaction in Change Commitment

Abstract: Managerial transformational leadership skills may directly influence banking counter staff toward change commitment and improve job satisfaction and service quality, or the influence instead may be mediated by change commitment. For a sample comprised of 246 managers from four large Taiwanese banks, the following path relationships were tested: (1) the association of transformational leadership with change commitment, (2) the association of change commitment with job satisfaction, and (3) the direct or indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
(89 reference statements)
1
16
0
Order By: Relevance
“…Herscovitch and Meyer’s (2002) 18-item Change Commitment Scale (overall α = .85) was applied for evaluation of commitment scale in the workplace. Previous studies found a Cronbach’s α ranging from .79 to .93 (Herold et al., 2008; Yang, 2011a, 2011b). Using the same three-factor construct, the Cronbach’s α found in the current study was .85 (Guttman split-half coefficient = .77).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Herscovitch and Meyer’s (2002) 18-item Change Commitment Scale (overall α = .85) was applied for evaluation of commitment scale in the workplace. Previous studies found a Cronbach’s α ranging from .79 to .93 (Herold et al., 2008; Yang, 2011a, 2011b). Using the same three-factor construct, the Cronbach’s α found in the current study was .85 (Guttman split-half coefficient = .77).…”
Section: Methodsmentioning
confidence: 99%
“…Proximal-distal mediators Podsakoff et al (1990Podsakoff et al ( , 1996, Dirks and Ferrin (2002), and Yang (2011aYang ( , 2014a reported that leadership trust and change commitment played individual mediating roles in relation to the leadership-job satisfaction connection (Braun et al, 2013;Anwar & Ahmad, 2012). Accordingly, from Models 5 and 6, we conclude there are two alternative paths linking three types of mediation.…”
Section: Stepsmentioning
confidence: 99%
See 2 more Smart Citations
“…In which one of these core values and concepts is leadership. A company's senior leaders need to set directions and create a customer focus, clear and visible values, and high expectations (Yang, 2011). The values, directions, and expectations should balance the needs of all stakeholders.…”
Section: Leadership Changementioning
confidence: 99%